2013
DOI: 10.2527/jas.2012-5918
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic infusion of leptin and nutrition on sexual maturation of zebu heifers1

Abstract: ABSTRACT:The amount of fat in the carcass has been proposed as a regulator of initiation of puberty in cattle. To test if changes in energy intake and in circulating leptin concentration are each capable of altering age, BW, and body composition at puberty, 36 prepubertal Nellore heifers, 18 to 20 mo old, 275.8 ± 17.2kg BW, and BCS of 5 ± 0.5 (1 to 9 scale), were randomly assigned to each of 3 treatments (n = 12): High (high energy diet), Low (low energy diet), and LL [low energy diet + ovine leptin (oLeptin)]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
3
0
2
Order By: Relevance
“…Furthermore, administration of recombinant ovine leptin stimulated secretion of GnRH and LH in undernourished heifers, but was not capable of accelerating puberty onset in well-nourished heifers Zieba et al, 2004). However recent findings show that although exogenous administration of leptin temporarily enhanced the rate of follicular growth, it does not accelerate puberty (Carvalho et al, 2013). Collectively these data indicate that while leptin plays an important role as a signal linking nutritional status to the central reproductive axis in cattle, other factors are also involved.…”
Section: Suckling-maternal Bondmentioning
confidence: 66%
“…Furthermore, administration of recombinant ovine leptin stimulated secretion of GnRH and LH in undernourished heifers, but was not capable of accelerating puberty onset in well-nourished heifers Zieba et al, 2004). However recent findings show that although exogenous administration of leptin temporarily enhanced the rate of follicular growth, it does not accelerate puberty (Carvalho et al, 2013). Collectively these data indicate that while leptin plays an important role as a signal linking nutritional status to the central reproductive axis in cattle, other factors are also involved.…”
Section: Suckling-maternal Bondmentioning
confidence: 66%
“…Leptin can inhibit NPY expression (Gamba et al 2006), modulate the expression of kisspeptin receptors (Stephens et al 2015), and then hasten puberty. However, although chronic administration of recombinant leptin increased leptin concentration, it did not increase the frequency of LH pulses nor anticipated puberty in beef heifers (Maciel et al 2004;Carvalho et al 2013). Therefore, it is assumed that leptin is not responsible for puberty triggers, but acts as a permissive signal for puberty (Maciel et al 2004;Barb et al 2004).…”
Section: Discussionmentioning
confidence: 89%
“…Leptin administration restores normal LH pulses in fasted animals (Amstalden et al, 2000). Carvalho et al (2013) reported higher expression of the leptin gene on adipose tissue in heifers fed high-energy diets; therefore, heifers with more adipose tissue can synthetize more leptin.…”
Section: Discussionmentioning
confidence: 99%